Photoelectric glass material with high spectral transmittance as well as preparation method and application thereof
By adopting glass compositions with specific chemical composition and chemical reinforcement treatment, photoelectric glass materials with high spectral transmittance and excellent mechanical properties are prepared, which solves the shortcomings of existing photoelectric glass materials in terms of spectral transmittance and mechanical strength, and is suitable for high-performance optical systems and detection systems.
Patent Information
- Application Number
- CN202411362789.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-05-02
AI Technical Summary
The existing photoelectric glass materials have low light transmittance in the ultraviolet, visible and near-infrared spectral ranges, which cannot meet the needs of high-performance optical systems and detection systems for wide spectrum high light transmittance. At the same time, there are problems such as insufficient stray light elimination ability, impure glass internal quality and insufficient mechanical intensity.
The glass composition after chemical reinforcement treatment was used to prepare the photoelectric glass material by high temperature melting, stirring, clarification, molding and annealing.
It has achieved high spectral transmittance, excellent in-spectral transmission ratio, effective stray light elimination, excellent glass quality and high mechanical strength, and is suitable for high-performance cameras, spatial vision imaging detection systems and other fields.
Smart Images

Figure CN119912157A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of glass technology, and specifically to a glass material, especially a photoelectric glass material with high spectral transmittance, and a preparation method and application thereof. Background Art
[0002] Any discussion of the prior art throughout the specification should not be considered as an admission that such prior art is widely known or forms part of the common general knowledge in the field.
[0003] Photoelectric glass is a new type of special glass. This glass can generate a high-efficiency absorption layer with no reflection interface with the substrate glass around the effective area through self-substrate generation technology, which makes it the preferred optical input window material in optical systems and photoelectric detection systems. With the advancement of science and technology, photoelectric glass has been widely used in aerospace, national defense and military, astronomical observation, engineering monitoring and other fields. At the same time, it is very useful in high-performance cameras, space visual imaging detection systems, urban Skynet monitoring systems, underground mine search and rescue, high-end personal equipment, etc. These applications put forward higher requirements for photoelectric glass window materials, and its light-transmitting area needs to have high transmittance in the ultraviolet, visible and near-infrared spectrum ranges. Therefore, it is of great significance to develop a photoelectric glass material with high spectral transmittance.
[0004] Existing technologies have obvious defects in the spectral transmittance, spectral transmittance, stray light elimination capability, glass internal purity and mechanical strength of optoelectronic glass materials, and cannot meet the needs of high-performance optical systems and detection systems, especially in the application field of intelligent technology, such as high-performance cameras, space visual imaging detection systems, urban Skynet monitoring systems, underground mine search and rescue, high-end personal equipment and other fields.
[0005] For example, the transmittance of existing optoelectronic glass materials in the ultraviolet, visible and near-infrared spectral ranges is generally not high, which cannot meet the needs of high-performance optical systems and detection systems for wide spectrum and high transmittance. For example, many existing materials have low spectral transmittance in the range of 350nm to 1000nm, resulting in unstable performance of optical systems in this wavelength range. For example, the spectral transmittance of current optoelectronic glass materials is uneven, which affects the imaging quality and detection accuracy of optical systems. For high-performance cameras and space vision imaging detection systems, consistent and efficient spectral transmittance is the key to ensuring image clarity and detection accuracy. The presence of stray light can seriously affect the signal-to-noise ratio and detection sensitivity of optoelectronic systems. The improvement of existing optoelectronic glass materials in stray light elimination is limited, resulting in limited overall performance of optical systems, especially in applications with high photosensitivity and high precision requirements. In addition, due to production process limitations, existing optoelectronic glass materials are prone to defects such as bubbles, inclusions and stress concentration. These inherent defects not only reduce the optical properties of glass, but also affect its mechanical strength and durability. For example, the presence of bubbles and inclusions can cause light scattering and absorption, reducing the overall light transmittance and imaging quality of the glass. Also, existing optoelectronic glass materials are prone to cracking and damage under high-intensity use environments and cannot meet application requirements under harsh conditions. When high-performance optical systems and optoelectronic detection systems work in complex environments, glass materials need to have high bending strength and impact resistance to ensure long-term stable operation of the system.
[0006] Therefore, developing an excellent optoelectronic glass material is of great significance for improving the overall performance of optoelectronic systems and broadening their application areas. Summary of the invention
[0007] The purpose of the present invention is to provide a photoelectric glass material with high spectral transmittance, a preparation method and application thereof. The photoelectric glass material with high spectral transmittance provided by the present invention is a strengthened glass after chemical strengthening treatment, which has high spectral transmittance, excellent spectral transmittance, effective stray light elimination area, excellent glass internal quality and high mechanical strength, and plays an important role in high-performance cameras, space visual imaging detection systems, urban skynet monitoring systems, underground mine search and rescue, high-end personal equipment, etc.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] In a first aspect of the present invention, a glass composition is provided, which comprises or consists of the following components, in mass percentage: 55-65% SiO2, 0.1-3% Bi2O3, 8-18% Na2O, 1-6% K2O, 1-5% B2O3, 8-18% Al2O3, 2-5% ZrO2, 0-4% MgO, 0-3% CaO, and 1-3% Sb2O3.
[0010] In an embodiment of the present invention, silicon dioxide (SiO2) is a glass-forming oxide and is the main component of the glass skeleton network structure, and exists in the glass structure in the form of [SiO4] tetrahedrons. The amount of SiO2 not only affects the melting point and viscosity of the glass, but may also affect the redox reaction balance of the glass, the solubility and reactivity of the clarifier and other additives, and thus indirectly affect the formation and thickness of the absorption layer during the reduction treatment. In particular, under a reducing atmosphere, the content of SiO2 may affect the redox reaction in the glass melt, and then affect the formation and distribution of pigments or other absorption substances in the absorption layer, and then affect the properties and thickness of the absorption layer. Therefore, in the present invention, the content of SiO2 is 55-65% by mass. In some embodiments of the present invention, the content of SiO2 can be further selected from the following content ranges or be any value in the following content ranges: 55-58.1%, 55-60%, 55-62%, 55-65%, 58.1-59.9%, 58.1-59.8%, 58.1-59.7%, 58.1-59.6%, 58.1-59.5%, 58.1-59.4%, 58.1-59.3%, 58.1-59%, 58.1-60%, 58.1-61%, 58.1-62%, 58.1-63%, 58.1-65%, 60-62%, 60-65%, 62-65%, and the like.
[0011] In an embodiment of the present invention, bismuth oxide (Bi2O3) is an important additive, and the bismuth element in the glass can be reduced to bismuth in a low oxidation state or even metallic bismuth under a high temperature reducing atmosphere. This reduction process will cause a change in the color of the glass material, which may cause the glass to present a specific color, such as black or gray. In the present invention, the content of Bi2O3 is 0.1-3% by mass. In some embodiments of the present invention, the content of Bi2O3 can be further selected from the following content ranges or any value in the following content ranges: 0.1-1%, 0.1-2%, 0.1-3%, 1-2%, 1-3%, 1.1-3%, 2-3%, 2.1-3%, 2.2-3%, 2.3-3%, 2.4-3%, 2.5-3%, 2.6-3%, 2.7-3%, 2.8-3%, 2.9-3%, and the like.
[0012] In the embodiment of the present invention, sodium oxide (Na2O) and potassium oxide (K2O) are the network outer oxides of glass. Alkali metal ions are easy to move and diffuse in the glass body, and can reduce the viscosity of glass during high temperature melting, making the glass easy to melt. They are good fluxing agents. In addition, Na2O in the glass + It is a necessary condition for achieving chemical strengthening. In the present invention, the content of Na2O is 8-18% and the content of K2O is 1-6% by mass. In some embodiments of the present invention, the content of Na2O can be further selected from the following content ranges or any value in the following content ranges: 8-12%, 8-13%, 8-15%, 8-18%, 10-18%, 12-13%, 12-15%, 12-18%, 13-15%, 13.1-15%, 13.3-15%, 13.6-15%, 13.8-15%, 14-15%, 14.1-15% , 14.3-15%, 14.6-15%, 14.8-15%, 13-18%, 15-18%, 15-15.3%, 15-15.6%, 15-15.8%, 15-16%, 15-16.1%, 15-16.3%, 15-16.6%, 15-16.8%, 15-17%, 15-17.1%, 15-17.3%, 15-17.6%, 15-17.8%, and so on. In some embodiments of the present invention, the content of K2O can be further selected from the following content ranges or any value in the following content ranges: 1-2%, 1-2.9%, 1-3%, 1-3.9%, 1-5%, 1-6%, 2-3%, 2-3.9%, 2-6%, 3-3.9%, 3-6%, 3.9-6%, 1.1-2%, 1.3-2%, 1.5-2%, 1.6-2%, 1.8-2%, 2-2.9%, 2-2.8%, 2-2.6%, 2-2.5%, 2-2.3%, 2-2.1%, and the like.
[0013] In some embodiments of the present invention, the preferred content ratio of Na2O to K2O is 2-13: 1. The ratio can be further selected from: 4-13: 1, 5-13: 1, 6-13: 1, 7-13: 1, 4-8: 1, 4-7.5: 1, and the like.
[0014] In some embodiments of the present invention, the preferred sum of the contents of Na2O and K2O is 11-21.9%. The ratio can be further selected from: 14-21.9%, 14-20%, 14-18%, 14-17%, 15-17%, 16-17%, and the like.
[0015] In an embodiment of the present invention, boron trioxide (B2O3) is a glass-forming oxide, and B can replace part of Si in silicate glass to form a network structure. In addition, B2O3 has a fluxing effect in glass, which can reduce the high-temperature viscosity of glass, save costs, and facilitate production. However, as the content of B2O3 increases, the devitrification range of glass increases, and B2O3 is volatile and can cause pollution to the environment, so the amount should be strictly controlled during the production process. In the present invention, the content of B2O3 is 1-5% by mass. In some embodiments of the present invention, the content of B2O3 can be further selected from the following content ranges or any value in the following content ranges: 1-2%, 1-3%, 1-4%, 1-5%, 2-2.5%, 2-3%, 2-4%, 2-5%, 3-4%, 3-5%, 4-5%, 1.1-2%, 1.3-2%, 1.5-2%, 1.6-2%, 1.7-2%, 1.8-2%, 2-2.9%, 2-2.8%, 2-2.6%, 2-2.5%, 2-2.3%, 2-2.2%, 2-2.1%, and the like.
[0016] In the embodiment of the present invention, aluminum oxide (Al2O3) is a glass intermediate oxide, and its content affects the thermal expansion coefficient and chemical and thermal stability of the glass. Al2O3 can increase the mechanical processing performance of the glass, but too much will reduce the material properties. In addition, the volume of [AlO4] in the glass is 41cm 3 / mol, the volume of [SiO4] is 27cm 3 / mol, [AlO4] is 52% larger in volume than [SiO4], so [AlO4] will cause the glass voids to increase, which is beneficial to improve the ion exchange efficiency and make the glass material have excellent chemical strengthening properties. In the present invention, the content of Al2O3 is 8-18% by mass. In some embodiments of the present invention, the content of Al2O3 can be further selected from the following content ranges or any value in the following content ranges: 8-10%, 8.1-10%, 8.3-10%, 8.5-10%, 8.6-10%, 8.8-10%, 9-10%, 9.1-10%, 8.3-10%, 9.5-10%, 9.6-10%, 9.8-10%, 10-11.9%, 10 -11.7%, 10-11.6%, 10-11.5%, 10-11.3%, 10-11.1%, 10-11%, 10-10.9%, 10-10.8%, 10-10.6%, 10-10.5%, 10-10.3%, 10-10.2%, 8-12%, 8-15%, 8-18%, 10-12%, 10-15%, 10-18%, 12-18%, etc.
[0017] In an embodiment of the present invention, zirconium dioxide (ZrO2) is a glass intermediate oxide, which has the effect of improving chemical stability and preventing alkali metal and alkaline earth metal ions from being exposed. It is also an important component for improving the tensile elastic modulus, and is very helpful for improving the hardness of glass after chemical strengthening. In the present invention, the content of ZrO2 is 2-5% by mass. In some embodiments of the present invention, the content of ZrO2 can be further selected from the following content ranges or any value in the following content ranges: 2-3%, 2-5%, 3-5%, 3.1-5%, 3.3-5%, 3.5-5%, 3.6-5%, 3.8-5%, 4-5%, 4.1-5%, 4.3-5%, 4.5-5%, 4.6-5%, 4.8-5%, 4.9-5%, and the like.
[0018] In an embodiment of the present invention, magnesium oxide (MgO) and calcium oxide (CaO) are alkaline earth metal oxides, and the addition of alkaline earth metal oxides can greatly reduce the phase separation tendency of glass. At the same time, MgO is added on the basis of alkali-aluminosilicate glass, which has a network breaking and fluxing effect on the glass, and does not cause substantial disconnection of the network, and can promote the formation of multi-rings in the network structure, including ternary rings, tetracyclic rings, pentacyclic rings and hexacyclic rings, etc., which not only meets the integrity of the glass connection, but also helps to create gaps between glass structural units, creates exchange channels for ion exchange, and is conducive to the increase of the depth of the compressive stress layer (DOL) after chemical strengthening, thereby improving the bending strength and overall impact resistance of the glass. In the present invention, the content of MgO is 0-4% and the content of CaO is 0-3% by mass. In some embodiments of the present invention, the content of MgO can be further selected from the following content ranges or any value in the following content ranges: 0, 0-1%, 0-1.9%, 0-3%, 0-4%, 1.1-1.9%, 1.3-1.9%, 1.5-1.9%, 1.6-1.9%, 1.7-1.9%, 1.8-1.9%, 1.9-2.9%, 1.9-2.8%, 1.9-2.6%, 1.9-2.5%, 1.9-2.3%, 1.9-2.1%, 1.9-2%, 1-1.9%, 1-3%, 1-4%, 1.9-3%, 1.9-4%, 3-4%, and the like. In some embodiments of the present invention, the CaO content can be further selected from the following content ranges or any value in the following content ranges: 0, 0-1%, 0-2%, 1-1.5%, 1-2%, 1-3%, 1.1-2%, 1.3-2%, 1.5-2%, 1.6-2%, 1.8-2%, 2-2.1%, 2-2.3%, 2-2.5%, 2-2.6%, 2-2.8%, 2-2.9%, 2-3%, and the like.
[0019] In some embodiments of the present invention, MgO and CaO are not zero at the same time.
[0020] In some embodiments of the present invention, the content of MgO is not higher than the content of CaO.
[0021] In the present invention, there is a synergistic and complementary effect between MgO and CaO. The combination of the breaking flux effect of MgO and the hardness and mechanical strength improvement effect of CaO can significantly optimize the overall performance of the glass. MgO helps to form a variety of ring structures and improve the chemical strengthening effect, while CaO can improve the mechanical properties and forming properties of the glass. The combination of the two can effectively avoid the adverse effects of too high or too low a single component, and ensure the balance and optimization of the performance of the glass in all aspects. Therefore, in the glass formula, it is necessary to control the content ratio of MgO and CaO to ensure the best performance of their synergistic effect. In some embodiments of the present invention, the sum of the optimal contents of MgO and CaO is 1-6%. In some optional embodiments, the sum of the contents of MgO and CaO is 3-6%, 3-3.9%, 3.9-6%, 1-3.9%, 1-3%, 3.9-4%, 3.9-5%, 3.9-5.9%, 3.9-5.5%, 3.9-5.1%, 3.9-4.9%, 3.9-4.6%, 3.9-4.5%, 3.9-4.3%, 3.9-4.1%, 3.1-3.9%, 3.3-3.9%, 3.5-3.6%, 3.6-3.9%, 3.7-3.9%, or 3.8-3.9%.
[0022] In an embodiment of the present invention, antimony trioxide (Sb2O3) is not only used as a clarifier and bubble inhibitor in glass manufacturing. Under high temperature conditions, antimony trioxide will be reduced to antimony dioxide, while oxidizing some impurity elements in the glass. Subsequently, antimony dioxide is oxidized back to antimony trioxide, forming a redox cycle. This cycle continuously oxidizes and removes impurities in the glass, thereby improving the clarity of the glass. In addition, antimony trioxide also has the effect of inhibiting the formation of bubbles. At high temperatures, glass raw materials may contain oxides or other impurities, which will form bubbles and affect the transparency of the glass. Antimony trioxide can reduce these oxides or impurities, prevent bubble formation, and thus improve the quality of the glass. In the present invention, the content of Sb2O3 is 1-3% by mass. In some embodiments of the present invention, the content of Sb2O3 can be further selected from the following content ranges or be any value in the following content ranges: 1-1.9%, 1-1.8%, 1-1.7%, 1-1.6%, 1-1.5%, 1-1.4%, 1-1.3%, 1-1.2%, 1-1.1%, 1-2%, 1-3%, 2-3%, and the like.
[0023] In an embodiment of the present invention, Sb2O3 and Al2O3 act synergistically in the glass manufacturing process, and the combined use of the two can significantly improve the mechanical strength and chemical resistance of the glass. Antimony trioxide effectively clarifies the glass and reduces the formation of impurities and bubbles through its redox cycle, while alumina provides additional chemical stability and physical strength. Specifically, alumina acts as a network former in the glass structure, making the silicate structure of the glass more stable, thereby enhancing the hardness and wear resistance of the glass. At the same time, alumina improves the thermal shock resistance of the glass, making it more stable and less prone to breakage under high temperature conditions. Sb2O3 reduces bubbles and impurities in the glass through a clarifying effect, and these impurities are often weak points in the performance of the glass. By eliminating these weak points, the overall mechanical strength and durability of the glass are further improved. In some embodiments of the present invention, the sum of the preferred Al2O3 and Sb2O3 contents is 9-19%. In some optional embodiments, the content of Al2O3 and Sb2O3 is 9-15%, 9-12%, 9-11%, 10-11%, 10.1-11%, 10.3-11%, 10.6-11%, 10.8-11%, 11-12%, 11-11.9%, 11-11.5%, 11-11.6% or 11-11.8%.
[0024] In some embodiments of the present invention, the glass composition, in terms of mass percentage, comprises: 55-65% SiO2, 0.1-3% Bi2O3, 8-18% Na2O, 1-6% K2O, 1-5% B2O3, 8-18% Al2O3, 2-5% ZrO2, 1-4% MgO, 0 or 1-3% CaO, and 1-3% Sb2O3.
[0025] In some embodiments of the present invention, the glass composition, in terms of mass percentage, comprises: 58.1-65% SiO2, 1-3% Bi2O3, 8-18% Na2O, 1-6% K2O, 1-5% B2O3, 8-15% Al2O3, 2-5% ZrO2, 1-4% MgO, 0-3% CaO, and 1-3% Sb2O3.
[0026] In some embodiments of the present invention, the glass composition, in terms of mass percentage, comprises: 58-65% SiO2, 2-3% Bi2O3, 12-15% Na2O, 1-3% K2O, 1-5% B2O3, 8-15% Al2O3, 2-5% ZrO2, 1-2.5% MgO, 0-2% CaO, and 1-3% Sb2O3.
[0027] The various specific technical features described in the above embodiments of the present invention can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further explain various possible combinations.
[0028] Unless otherwise specified, the numerical range described in the present invention includes all the numerical values within this range, and includes the range value composed of any two numerical values within this range. For example, 0.1-2%, this numerical range includes all the numerical values between 0.1-2%, and includes the range value (0.11-0.19%) composed of any two numerical values within this range (for example: 0.11%, 0.19%); different numerical values of the same indicator appearing in all embodiments of the present invention can be arbitrarily combined to form a range value.
[0029] In a second aspect of the present invention, a photovoltaic glass blank is provided, which is made of the glass composition described in the first aspect.
[0030] The preparation method of the optoelectronic glass blank comprises: mixing raw materials, melting at a high temperature of 1500-1600° C., stirring, clarifying, cooling to 1330-1420° C. for forming, and annealing at 440-550° C. after forming to obtain the photoelectric glass blank.
[0031] The raw materials may also be selected from the following materials as needed: quartz sand, bismuth oxide (or bismuth nitrate pentahydrate), sodium carbonate (or sodium nitrate), potassium carbonate (or potassium nitrate), boric oxide (or boric acid), aluminum hydroxide (or aluminum trioxide), zirconium oxide, calcium oxide (or calcium carbonate), magnesium oxide (or basic magnesium carbonate) and antimony trioxide.
[0032] In an embodiment of the present invention, the minimum spectral transmittance of the optoelectronic glass blank to light with a wavelength of 350-1000 nm is ≥99.80%, preferably ≥99.9%. In some embodiments of the present invention, the minimum spectral transmittance of the optoelectronic glass blank to light with a wavelength of 350-1000 nm can reach 99.8-99.92%, 99.85-99.92%, 99.88-99.92% or 99.91-99.92%.
[0033] In an embodiment of the present invention, the photovoltaic glass blank has excellent glass internal quality, and the bubble degree meets the A0 level.
[0034] In a third aspect of the present invention, there is provided a photoelectric glass material, which comprises a light-transmitting base glass and a light-absorbing layer;
[0035] The light absorbing layer covers part of the surface of the light-transmitting base glass, and divides the surface of the light-transmitting base glass into a low light-transmitting area and at least one light-transmitting effective area; wherein the light-transmitting effective area is not covered with the light absorbing layer, allowing the target light to pass through; and the low light-transmitting area covers the light absorbing layer to absorb or block the target light;
[0036] The light-transmitting base glass has a composition of the glass composition as described in the first aspect, or is made of the glass blank as described in the second aspect.
[0037] The light absorbing layer is obtained by reducing the light-transmitting substrate glass and is generally formed on the surface of the light-transmitting glass substrate.
[0038] By testing the transmittance in the range of 350-1000nm, the light transmittance of the material in the entire visible light and part of the near-infrared spectrum can be comprehensively evaluated. This is crucial to ensure that the material maintains a consistent high transmittance under various lighting conditions. And by detecting the transmittance in the entire spectral range, the optical uniformity and consistency of the material can be identified to avoid optical distortion or performance fluctuations caused by material inhomogeneity. In an embodiment of the present invention, the minimum spectral transmittance of the light-transmitting effective area for 350-1000nm wavelength light is ≥99.80%, preferably ≥99.9%, which ensures high transmittance of light in a wide band. Such performance enables the optoelectronic glass material of the present invention to provide clear and bright images in applications such as high-performance cameras and space visual imaging detection systems, improve imaging quality, reduce light loss, and is suitable for various optical imaging and monitoring equipment. In some embodiments of the present invention, the minimum spectral transmittance of the light-transmitting effective area to light with a wavelength of 350-1000 nm can reach 99.8-99.92%, 99.85-99.92%, 99.88-99.92% or 99.91-99.92%.
[0039] In an embodiment of the present invention, the thickness of the absorption layer is ≥488 μm, preferably ≥518 μm, and more preferably ≥528 μm. Such a thickness ensures the stability and consistency of the absorption layer. The thick and stable absorption layer can maintain the optical properties and durability of the material in harsh environments and improve the reliability of the device. In some embodiments of the present invention, the thickness of the absorption layer is 488-532 μm, 499-532 μm, 500-532 μm, 507-532 μm, 518-532 μm, 520-532 μm or 528-532 μm.
[0040] 500nm is approximately located in the center of the visible spectrum, which is an area where the human eye is more sensitive to light. Testing the transmittance of this band helps to evaluate the performance of the material in the visible light range. In an embodiment of the present invention, the spectral transmittance of the light absorbing layer (low transmittance area) to 500nm wavelength light is ≤1%, preferably ≤0.9%, and more preferably ≤0.8%. This shows that the photoelectric glass material of the present invention can effectively eliminate stray light. In fields such as urban Skynet monitoring systems and high-end personal equipment, stray light elimination can improve image contrast and clarity, and enhance the performance of monitoring and visual equipment under complex light conditions. In some embodiments of the present invention, the spectral transmittance of the light absorbing layer to 500nm wavelength light can be controlled at 0.75-1%, 0.75-0.93%, 0.75-0.9%, 0.75-0.86%, and 0.75-0.82%.
[0041] In an embodiment of the present invention, the optoelectronic glass material has excellent glass internal quality, and the bubble degree meets the A0 level, which indicates that there are no obvious bubbles inside the material and that high-quality optical performance can be maintained. In applications such as precision optical instruments and high-end camera lenses, bubble-free high-quality glass can provide distortion-free optical performance, which ensures that the optoelectronic glass material of the present invention can be suitable for high-precision imaging and detection.
[0042] Bending strength refers to the ability of a material to resist deformation and damage when subjected to bending stress. For optoelectronic glass materials, high bending strength is crucial because it directly affects the durability, reliability, safety and applicability of the material. In an embodiment of the present invention, the bending strength of the optoelectronic glass material after chemical strengthening is ≥200MPa, preferably ≥210MPa, and more preferably ≥220MPa. The optoelectronic glass material of the present invention has high bending strength, which ensures that the glass maintains its structural integrity and functionality under various physical stresses, and can avoid breakage or deformation caused by bending stress. This property makes optoelectronic glass materials have significant advantages in the fields of high-performance cameras, space visual imaging detection systems, urban Skynet monitoring systems, underground mine search and rescue, and high-end personal equipment, such as improving image quality, increasing equipment durability, enhancing protective performance, and optimizing lightweight design, thereby significantly improving the performance and application value of related equipment. In some embodiments of the present invention, the bending strength of the photovoltaic glass material after chemical strengthening can be controlled within 200-221 MPa, 208-221 MPa, 215-221 MPa, 216-221 MPa, or 218-226 MPa.
[0043] In a fourth aspect of the present invention, a method for preparing the optoelectronic glass material described in the third aspect is provided, comprising:
[0044] The raw materials are mixed, melted at a high temperature of 1500-1600°C, stirred, clarified, and then cooled to 1330-1420°C for molding. After molding, they are annealed at 440-550°C to obtain a photoelectric glass blank. The photoelectric glass blank is machined into a certain size to serve as a light-transmitting glass substrate.
[0045] Then, the light-transmitting glass substrate is subjected to a reduction treatment to form a light absorption layer on the surface of the glass material, wherein the reduction treatment is carried out in a reducing atmosphere, the reduction treatment time is 5000-15000 min, the pressure is 0.01-0.3 MPa, and the temperature is 550-700° C.;
[0046] Mechanical processing is performed on the photovoltaic glass material with a light absorption layer formed on the surface, the purpose of which is to process the formed light absorption layer so as to expose the light-transmitting effective area as required;
[0047] The mechanical processing described in the present invention includes conventional processing operations such as grinding, polishing, fine carving, chamfering, and cutting, and its purpose is to improve the surface quality of the glass to ensure the effect of the subsequent reduction treatment, or to make the glass blank reach a specific shape and size to meet the needs of specific applications and ensure the convenience of subsequent processing and use. Therefore, appropriate processing methods can be selected according to the needs of subsequent operations. For example, through grinding and polishing, the glass surface is made more balanced and smooth, or through cutting, the glass is made to reach the expected size and shape.
[0048] Furthermore, the method further comprises the step of chemically strengthening the machined optoelectronic glass material, wherein the chemical strengthening is performed at a temperature of 350-450° C. for a time of 100-600 min, and the chemical strengthening is performed by an ion exchange method, and the salt bath used may be at least one molten salt of lithium salt, sodium salt, and potassium salt. For example, in some embodiments, the molten salt is molten potassium nitrate.
[0049] The method provided by the present invention has process stability, and the glass material prepared by this method can maintain its excellent performance characteristics. Specifically, within the range of process parameters described in the present invention (such as temperature, time, pressure, etc.), appropriate adjustment of these parameters will not cause significant fluctuations in glass performance, thereby ensuring the consistency and reliability of the product. It is worth noting that within the range of process parameters disclosed in the present invention, appropriately increasing the temperature can accelerate the process, thereby shortening the preparation time. However, when selecting a higher temperature for operation, those skilled in the art know that it is necessary to comprehensively consider equipment capacity, energy consumption costs, and glass quality control to ensure that the excellent performance of the product is maintained while improving production efficiency.
[0050] In a fifth aspect of the present invention, an optical element is provided, which is made of the optoelectronic glass composition described in the first aspect or the optoelectronic glass blank described in the second aspect, or includes the optoelectronic glass material described in the third aspect.
[0051] In an embodiment of the present invention, the optical element includes but is not limited to an optical lens, a filter, an input window such as a sensor window, a spectacle lens, and the like.
[0052] In a sixth aspect of the present invention, a cover glass is provided, which is made of the optoelectronic glass composition described in the first aspect or the optoelectronic glass blank described in the second aspect, or includes the optoelectronic glass material described in the third aspect.
[0053] In the seventh aspect of the present invention, a lens is provided, which is made of the optoelectronic glass composition described in the first aspect or the optoelectronic glass blank described in the second aspect, or it contains the optoelectronic glass material described in the third aspect or the optical element described in the fifth aspect or the cover glass described in the sixth aspect.
[0054] In the eighth aspect of the present invention, there is provided an application of the glass composition described in the first aspect, the optoelectronic glass blank described in the second aspect, the optoelectronic glass material described in the third aspect, the optical element described in the fifth aspect, the cover glass described in the sixth aspect, or the lens described in the seventh aspect in the field of intelligent technology applications.
[0055] In the embodiments of the present invention, the application fields of the intelligent technology involve but are not limited to high-performance cameras, space visual imaging detection systems, urban Skynet monitoring systems, underground mine search and rescue, high-end personal equipment, etc. Specific applications include but are not limited to the manufacture of camera lenses, optical windows of satellite imaging systems, lenses of drone vision systems, surveillance camera lenses, windows of mine detection equipment, optical elements of rescue lighting equipment, lenses of smart glasses, lenses of outdoor sports cameras, display screen protection glass, etc.
[0056] Through one or more of the above technical means, the following beneficial effects can be achieved:
[0057] The present invention provides a photoelectric glass material with high spectral transmittance, a preparation method and application thereof. As a photoelectric glass material, the material has a wide spectral range and high spectral transmittance, the minimum spectral transmittance in the effective area is ≥99.80% (@350-1000nm), it has an effective stray light elimination area, the transmittance of the light absorption layer is ≤1% (@500nm), it has excellent glass internal quality, the bubble degree meets the A0 level, and it has chemical strengthening characteristics. After chemical strengthening, the bending strength of the glass is ≥200MPa. It has broad application prospects in the field of intelligent technology applications, especially in high-performance cameras, space visual imaging detection systems, urban skynet monitoring systems, underground mine search and rescue, high-end personal equipment and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] The drawings constituting part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. The implementation scheme of the present application is described in detail below in conjunction with the drawings, wherein:
[0059] Figure 1 A comparison chart of the minimum spectral transmittance (1 mm thickness, @350-1000 nm) of the effective region of the photovoltaic glass of Examples 1-6 of the present invention and Comparative Examples 1-8 is shown.
[0060] Figure 2 A comparison chart of the transmittance (@500nm) of the absorption layer of the photovoltaic glass of Examples 1-6 of the present invention and Comparative Examples 1-8 is shown.
[0061] Figure 3 A comparison chart of the bending strength (after strengthening) of the photovoltaic glass of Examples 1-6 of the present invention and Comparative Examples 1-8 is shown. DETAILED DESCRIPTION
[0062] The present application is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.
[0063] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in this application can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in this application are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the content described herein can be applied to the method of this application. The preferred implementation methods and materials described in the text are for demonstration purposes only.
[0064] In the following embodiments of the present invention, unless otherwise specified, the following methods (standards) are used to test the performance of the products:
[0065] The transmittance of the glass sample was measured using a Shimadzu UV-visible spectrophotometer (UV-3600Plus). The test wavelength range was 350nm-1000nm, the surface of the tested glass sample was optically polished, and the test sample thickness was 1mm and 2mm.
[0066] The spectral transmittance of the sample under test is calculated by formula (1):
[0067]
[0068] Where: τ λ is the spectral internal transmittance of a sample with a thickness of λ; T 1λ is the spectral transmittance of a sample with a thickness of 1λ; T 2λ is the spectral transmittance of a sample with a thickness of 2λ; and, λ = 1λ - 2λ; for example, (GB / T 7962.12-2010).
[0069] The bending strength of the glass sample is measured using a three-point bending tester. The sample size is 3mm×4mm×40mm. The four long sides of the tested glass sample are optically polished, the long edges are chamfered, and the end surface of the test sample does not require special treatment. (GB / T 6569-2006)
[0070] The bubble density is defined as the volume per 100 cm 3 The degree of inclusions such as bubbles and stones contained in the glass, including their diameter and the total cross-sectional area of all bubbles, stones and other inclusions. (GB / T 7962.8-2010)
[0071] Among them, the bubble degree A0 means the total cross-sectional area of bubbles with a diameter of Φ≥0.05mm>0.03-0.10mm 2 / 100cm 2 ;
[0072] The bubble degree A means that the total cross-sectional area of the bubble with diameter Φ≥0.05mm is greater than 0.1-0.25mm 2 / 100cm 2 ;
[0073] Bubble degree B means the total cross-sectional area of bubbles with diameter Φ≥0.05mm>0.25-0.5mm 2 / 100cm 2 .
[0074] Example 1
[0075] The glass blank of this embodiment is composed of the following components in mass percentage: 55% SiO2, 0.1% Bi2O3, 18% Na2O, 3.9% K2O, 4% B2O3, 8% Al2O3, 2% ZrO2, 4% MgO, 2% CaO, and 3% Sb2O3.
[0076] Quartz sand, bismuth oxide, sodium carbonate, potassium nitrate, boric acid, aluminum hydroxide, zirconium oxide, calcium carbonate, basic magnesium carbonate and antimony trioxide are used as raw materials. After each glass raw material is mixed in proportion, the batch material is melted at a high temperature of 1500°C, clarified with auxiliary stirring, mechanically formed at 1330°C, and annealed at 440°C to obtain a glass blank.
[0077] The obtained glass blank is processed into a truncated cone shape, and then in a hydrogen atmosphere, a reduction process is carried out at 8300min, 0.03MPa, and 660°C to form a light absorption layer on the surface of the truncated cone glass. The upper and lower surfaces of the truncated cone with the absorption layer formed on the surface are mechanically processed to remove the absorption layer on the upper and lower circular surfaces of the truncated cone (retain the absorption layer on the side of the truncated cone), and ensure that the parallelism of the upper and lower circular surfaces is ≤0.01mm, the coaxiality is ≤0.02mm, and the surface roughness is ≤10nm, wherein the mechanical processing includes grinding, polishing, fine carving, and chamfering. The glass obtained after mechanical processing is chemically strengthened in molten potassium nitrate at 445°C for 240min to obtain a photoelectric glass material. The test results are shown in Table 2.
[0078] Example 2
[0079] The glass blank of this embodiment is composed of the following components in mass percentage: 58.1% SiO2, 3% Bi2O3, 15% Na2O, 2% K2O, 2% B2O3, 10% Al2O3, 5% ZrO2, 1.9% MgO, 2% CaO, and 1% Sb2O3.
[0080] Quartz sand, bismuth oxide, sodium nitrate, potassium carbonate, boron oxide, aluminum oxide, zirconium oxide, calcium oxide, magnesium oxide and antimony trioxide were used as raw materials, and each glass raw material was mixed in proportion, and then a glass blank and a photovoltaic glass material were prepared according to the method in Example 1. The test results are shown in Table 2.
[0081] Example 3
[0082] The glass blank of this embodiment is composed of the following components in mass percentage: 60% SiO2, 2% Bi2O3, 13% Na2O, 1% K2O, 1% B2O3, 12% Al2O3, 2% ZrO2, 3% MgO, 3% CaO, and 3% Sb2O3.
[0083] Using quartz sand, bismuth nitrate pentahydrate, sodium carbonate, potassium nitrate, boric acid, aluminum hydroxide, zirconium oxide, calcium carbonate, basic magnesium carbonate and antimony trioxide as raw materials, glass blanks and photoelectric glass materials were prepared according to the method in Example 1. The test results are shown in Table 2.
[0084] Example 4
[0085] The glass blank of this embodiment is composed of the following components in mass percentage: 62% SiO2, 1% Bi2O3, 12% Na2O, 6% K2O, 3% B2O3, 10% Al2O3, 3% ZrO2, 1% CaO, and 2% Sb2O3.
[0086] Quartz sand, bismuth oxide, sodium carbonate, potassium nitrate, boric acid, aluminum hydroxide, zirconium oxide, calcium carbonate and antimony trioxide were used as raw materials, and each glass raw material was mixed in proportion, and then a glass blank and a photovoltaic glass material were prepared according to the method in Example 1. The test results are shown in Table 2.
[0087] Example 5
[0088] The glass blank of this embodiment is composed of the following components in percentage by mass: 65% SiO2, 2% Bi2O3, 13% Na2O, 3% K2O, 5% B2O3, 8% Al2O3, 2% ZrO2, 1% MgO, and 0.1% Sb2O3.
[0089] Quartz sand, bismuth oxide, sodium nitrate, potassium carbonate, boron oxide, aluminum oxide, zirconium oxide, magnesium oxide and antimony trioxide were used as raw materials, and each glass raw material was mixed in proportion, and then a glass blank and a photovoltaic glass material were prepared according to the method in Example 1. The test results are shown in Table 2.
[0090] Example 6
[0091] The glass blank of this embodiment is composed of the following components in mass percentage: 60% SiO2, 1% Bi2O3, 8% Na2O, 3% K2O, 1% B2O3, 18% Al2O3, 5% ZrO2, 1% MgO, 2% CaO, and 1% Sb2O3.
[0092] Quartz sand, bismuth nitrate pentahydrate, sodium carbonate, potassium nitrate, boric acid, aluminum hydroxide, zirconium oxide, calcium carbonate, basic magnesium carbonate and antimony trioxide were used as raw materials, and each glass raw material was mixed in proportion, and then a glass blank and a photovoltaic glass material were prepared according to the method in Example 1. The test results are shown in Table 2.
[0093] Comparative Examples 1-8
[0094] The glass compositions of Comparative Examples 1-8 are shown in Table 1. The raw materials were used to prepare glass blanks and photovoltaic glass materials according to the method of Example 1. The test results are shown in Table 3.
[0095] The compositions and properties of the glass samples of Examples 1-6 and Comparative Examples 1-8 of the present invention are shown in Table 1, Table 2 and Table 3, respectively.
[0096] Table 1 Composition of glass samples of Examples 1-6
[0097] Composition / wt% Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 <![CDATA[SiO2]]> 55.0 58.1 60.0 62.0 65.0 60.0 <![CDATA[Bi2O3]]> 0.1 3.0 2.0 1.0 2.0 1.0 <![CDATA[Na2O]]> 18.0 15.0 13.0 12.0 13.0 8.0 <![CDATA[K2O]]> 3.9 2.0 1.0 6.0 3.0 3.0 <![CDATA[B2O3]]> 4.0 2.0 1.0 3.0 5.0 1.0 <![CDATA[Al2O3]]> 8.0 10.0 12.0 10.0 8.0 18.0 <![CDATA[ZrO2]]> 2.0 5.0 2.0 3.0 2.0 5.0 MgO 4.0 1.9 3.0 0 1.0 1.0 CaO 2.0 2.0 3.0 1.0 0 2.0 <![CDATA[Sb2O3]]> 3.0 1.0 3.0 2.0 1.0 1.0 total 100 100 100 100 100 100
[0098] Table 2 Glass sample composition of Comparative Examples 1-8
[0099]
[0100]
[0101] Table 3 Performance test results of glass samples of Examples 1-6
[0102]
[0103] Table 4 Performance test results of glass samples of Comparative Examples 1-8
[0104]
[0105] As can be seen from Table 3, the optoelectronic glass materials prepared in each embodiment have high spectral transmittance, excellent spectral transmittance, the minimum spectral transmittance in the effective area is ≥99.80% (@350-1000nm), has an effective stray light elimination area, the light absorption layer transmittance is ≤1% (@500nm), has excellent glass internal quality, the bubble degree meets the A0 level, and has chemically strengthened properties. The bending strength of the glass after chemical strengthening is ≥200MPa. In addition, the performance of the optoelectronic glass material of the present invention, such as spectral transmittance, spectral transmittance, bubble degree, absorption layer thickness, etc., is basically not affected by chemical strengthening treatment. In short, the above-mentioned excellent performance makes the glass material of the present invention show a wide range of application prospects in the fields of high-performance cameras, space visual imaging detection systems, urban skynet monitoring systems, underground mine search and rescue, high-end personal equipment, etc.
[0106] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. Although the present application is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A photovoltaic glass composition with high spectral transmittance, characterized in that, in terms of mass percentage, it comprises the following components: 55-65% SiO2, 0.1-3% Bi2O3, 8-18% Na2O, 1-6% K2O, 1-5% B2O3, 8-18% Al2O3, 2-5% ZrO2, 0-4% MgO, 0-3% CaO, and 1-3% Sb2O3, wherein: The contents of MgO and CaO are not equal to 0 at the same time.
2. The optoelectronic glass composition with high spectral transmittance according to claim 1, characterized in that: The composition includes, by mass percentage, 55-65% SiO2, 0.1-3% Bi2O3, 8-18% Na2O, 1-6% K2O, 1-5% B2O3, 8-18% Al2O3, 2-5% ZrO2, 1-4% MgO, 0 or 1-3% CaO, and 1-3% Sb2O3; Preferably, the composition comprises, by mass percentage, 58.1-65% SiO2, 1-3% Bi2O3, 8-18% Na2O, 1-6% K2O, 1-5% B2O3, 8-15% Al2O3, 2-5% ZrO2, 1-4% MgO, 0-3% CaO, and 1-3% Sb2O3; Preferably, the composition comprises, by mass percentage, 58-65% SiO2, 2-3% Bi2O3, 12-15% Na2O, 1-3% K2O, 1-5% B2O3, 8-15% Al2O3, 2-5% ZrO2, 1-2.5% MgO, 0-2% CaO, and 1-3% Sb2O3; Preferably, in terms of mass percentage, the ratio of Na2O to K2O is 2-13:1, preferably 4-13:1; Preferably, the sum of the contents of Na2O and K2O is 11-21.9% by mass, preferably 14-21.9%; Preferably, the sum of the contents of Al2O3 and Sb2O3 is 9-19% by mass, preferably 9-15%; Preferably, the sum of the contents of MgO and CaO is 1-6% by mass, preferably 1-4% by mass.
3. The optoelectronic glass composition with high spectral transmittance according to claim 1 or 2, characterized in that: In terms of mass percentage, the content of SiO2 is 55.1-65%, preferably 55.1-60% or 58-65%, more preferably 58-59.9%; Preferably, the content of Bi2O3 is 1-3% by mass, preferably 2-3%; Preferably, the content of Na2O is 10-18% by mass, preferably 12-18%, more preferably 12-15% or 15-17.9%; Preferably, the content of K2O is 1.1-6%, preferably 2-6%, more preferably 2-3% or 1.1-2% by mass percentage; Preferably, the content of B2O3 is 1.1-5%, preferably 2-3% or 1.1-2% by mass percentage; Preferably, the content of Al2O3 is 8-15% by mass, preferably 8-12%, more preferably 8-10% or 10-12%; Preferably, the content of ZrO2 is 2.1-5%, preferably 3-5%, more preferably 4-5%, by mass percentage; Preferably, the content of MgO is 0 or 1-4%, preferably 1-3%, more preferably 1-2% or 1.5-3% by mass percentage; Preferably, the content of CaO is 0-2.5% or 1-3% by mass, more preferably 0 or 2-3% or 1-2%; Preferably, in terms of mass percentage, the content of Sb2O3 is 1-2%, preferably 1-1.9%, and more preferably 1-1.5%.
4. A photovoltaic glass blank with high spectral transmittance, which is made of the photovoltaic glass composition with high spectral transmittance according to any one of claims 1 to 3; Preferably, the method for preparing the optoelectronic glass blank comprises: The raw materials are mixed, melted at a high temperature of 1500-1600°C, stirred, clarified, then cooled to 1330-1420°C for molding, and annealed at 440-550°C after molding to obtain the product.
5. A photoelectric glass material with high spectral transmittance, comprising a light-transmitting effective region and a light-absorbing layer, wherein the light-absorbing layer is obtained by reducing the light-transmitting effective region; in, The light-transmitting effective area is provided by a light-transmitting glass substrate, and the light-absorbing layer covers a part of the surface of the light-transmitting glass substrate, and the surface of the light-transmitting glass substrate is divided into a low light-transmitting area and at least one light-transmitting effective area; wherein the light-transmitting effective area is not covered with the light-absorbing layer, allowing the target light to pass through; and the low light-transmitting area is covered with the light-absorbing layer to absorb or block the target light Wherein, the composition of the light-transmitting glass substrate is the optoelectronic glass composition with high spectral transmittance as described in any one of claims 1 to 3, or is made of the optoelectronic glass blank with high spectral transmittance as described in claim 4; Preferably, the reduction treatment is carried out in a reducing atmosphere, the reduction treatment time is 5000-15000 min, the pressure is 0.01-0.3 MPa, and the temperature is 550-700° C.; Preferably, the minimum spectral transmittance of the effective area to light with a wavelength of 350-1000nm is ≥99.80%; the spectral transmittance of the absorption layer to light with a wavelength of 500nm is ≤1%; Preferably, the photovoltaic glass material has excellent glass internal quality, and the bubble degree meets the A0 level; Preferably, the bending strength of the photovoltaic glass material after chemical strengthening is ≥200MPa; Preferably, the temperature of the chemical strengthening is 350-450° C., the time is 100-600 min, and the salt bath used for chemical strengthening can be lithium salt, sodium salt, potassium salt or a mixed molten salt of the three.
6. A method for preparing the optoelectronic glass material with high spectral transmittance according to claim 5, characterized in that: include: The optoelectronic glass composition with high spectral transmittance according to any one of claims 1 to 3 is prepared by selecting raw materials, mixing the raw materials, melting them at a high temperature of 1500-1600° C., stirring, clarifying, then cooling them to 1330-1420° C. for forming, and annealing them at 440-550° C. after forming to obtain an optoelectronic glass blank; According to the needs, the photoelectric glass blank is mechanically processed into a light-transmitting glass substrate, and then a reduction treatment is performed to form an absorption layer on the surface of the light-transmitting glass substrate; According to the need, the light-transmitting glass substrate with the absorption layer formed on the surface is mechanically processed to expose the light-transmitting effective area; Preferably, the reduction treatment is carried out in a reducing atmosphere, the reduction treatment time is 5000-15000 min, the pressure is 0.01-0.3 MPa, and the temperature is 550-700° C.; Preferably, the method further comprises the step of chemically strengthening the machined optoelectronic glass material, wherein the temperature of the chemical strengthening is 350-450° C., the time is 100-600 min, and the salt bath used for chemical strengthening may be at least one molten salt selected from lithium salt, sodium salt and potassium salt.
7. An optical element, which is made of the optoelectronic glass composition with high spectral transmittance according to any one of claims 1 to 3 or the optoelectronic glass blank with high spectral transmittance according to claim 4, or comprises the optoelectronic glass material according to claim 5; Preferably, the optical element includes an optical lens, a filter, a sensor window, and a spectacle lens.
8. A cover glass, which is made of the optoelectronic glass composition with high spectral transmittance according to any one of claims 1 to 3 or the optoelectronic glass blank with high spectral transmittance according to claim 4, or comprises the optoelectronic glass material according to claim 5.
9. A lens, which is made of the optoelectronic glass composition with high spectral transmittance according to any one of claims 1 to 3 or the optoelectronic glass blank with high spectral transmittance according to claim 4, or it contains the optoelectronic glass material according to claim 5 or the optical element according to claim 7 or the cover glass according to claim 8.
10. Application of the optoelectronic glass composition with high spectral transmittance according to any one of claims 1 to 3, or the optoelectronic glass blank with high spectral transmittance according to claim 4, or the optoelectronic glass material according to claim 5, or the optical element according to claim 7, or the cover glass according to claim 8, or the lens according to claim 9 in the field of intelligent technology applications; Preferably, the application fields of the intelligent technology include high-performance cameras, space visual imaging detection systems, urban Skynet monitoring systems, underground mine search and rescue, and high-end personal equipment.